1995
DOI: 10.1161/01.cir.92.8.2327
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Control of the Force-Frequency Relation

Abstract: This article briefly reviews recent experimental studies which show that beta-adrenergic receptor stimulation produces an important enhancement of the force-frequency relation on myocardial contractility. The basic property of the force-frequency effect to progressively enhance myocardial contractility as heart rate increases is augmented at each level of increasing adrenergic stimulation. This newly described intrinsic mechanism for the control of cardiac inotropic state, graded beta-adrenergic amplification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(63 citation statements)
references
References 38 publications
4
58
0
1
Order By: Relevance
“…adrenergic stimulation caused a more positive force-frequency relationship (34). These studies demonstrated the importance of SR in establishing the force-frequency relationship.…”
Section: Atpase (Serca2) Protein (C) Quantitative Analysis Of Ncx (Bmentioning
confidence: 51%
“…adrenergic stimulation caused a more positive force-frequency relationship (34). These studies demonstrated the importance of SR in establishing the force-frequency relationship.…”
Section: Atpase (Serca2) Protein (C) Quantitative Analysis Of Ncx (Bmentioning
confidence: 51%
“…Hitherto, negative staircase (ie, the descending limb of function of the force-frequency relation) has been shown at high physiologic frequencies in rabbits and rats, 2,3,22 whereas a positive staircase by increasing HR (ie, enhancement of the force-frequency relation on myocardial contractility) has been demonstrated in dogs, pigs and humans. [22][23][24] In either case of a positive or negative staircase, amplification of the force-frequency effect by infusion of a -adrenergic receptor agonist has been reported. 22 Although this amplification of the force-frequency relation during administration of a -adrenergic agonist may provide an important mechanism influencing contractility, 25,26 it has not been demonstrated whether or not this phenomenon actually works in the sympathetic discharge.…”
Section: Cardiovascular Responses To Stimulation Frequency and Their mentioning
confidence: 99%
“…[22][23][24] In either case of a positive or negative staircase, amplification of the force-frequency effect by infusion of a -adrenergic receptor agonist has been reported. 22 Although this amplification of the force-frequency relation during administration of a -adrenergic agonist may provide an important mechanism influencing contractility, 25,26 it has not been demonstrated whether or not this phenomenon actually works in the sympathetic discharge. The present study showed that augmented sympathetic stimulation led to large increases in HR and contractility, followed by a decrease of the latter irrespective of increased norepinephrine release or the method of coronary perfusion.…”
Section: Cardiovascular Responses To Stimulation Frequency and Their mentioning
confidence: 99%
“…Because an increased HR would depress cardiac function in advanced HF through derangement of the force -frequency relation, 19,20 the effect of amiodarone on HR may augment pump function, and assist in tapering the dose of catecholamines or phosphodiesterase inhibitor. In the present study, amiodarone improved NYHA functional class and FS in 10 medically treated patients who were intolerant of -blockers.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies indicate that -adrenergic amplification of the forcefrequency effect on myocardial contractility is impaired in cardiac failure. 19,20 Moreover, isometrically contracting cardiac muscle taken from failing human hearts at the time of cardiac transplantation often shows a descending limb of the relation between increasing contraction frequency and peak tension. 21 Therefore, drugs with a negative chronotropic effect may augment cardiac function with respect to the force -frequency relation during the interim period before the late recovery of cardiac function after myocardial biological changes.…”
Section: Tolerability Of Amiodaronementioning
confidence: 99%